MAST CELL REACTION TO ACUPUNCTURE ON TONGUE - N. Pirovski; Y. Staykova-Pirovska; D. Atanasova; N. Dimitrov (Trakia Journal of Sciences)
PURPOSE: The aim is to find out the mast cells (MCs) reaction in tongue after experimental acupuncture. METHODS: For experiments were carried 10 adults rats (28 months age). The needles used for the acupuncture is 0.22x13mm, and were placed for 10 minutes into standard acupuncture point Ex-HN-10 (Juquan) corresponding to that of humans. This point is located on the upper surface in the sagittal plane of the tongue and is close to the center of the tongue body. As normal consequence of every acupuncture is the forming of a needle tract and also here in the tissues of the rats tongue we could demonstrate this. This was done with a visualization method for the needle tract that we developed for tongue. The proximity of the needle tract was examined for MCs. Two stains were used for proper visualization: Toluidine blue and Bismarck brown staining. RESULTS: In close proximity of the needle tract we observed degranulation of MCs that was massive and few destroyed MCs in the needle tract itself. At a considerable distance from the MCs some discharged granules from them was found. CONCLUSIONS: There is a MCs reaction on the acupuncture of tongue that includes a degranulation of the MCs that was massive in proximity of the acupuncture needle tract. Some of the effects ot acupuncture could be due to the demonstrated MCs degranulation.